An addressable packing parameter approach for reversibly tuning the assembly of oligo(aniline)-based supra-amphiphiles. Issue 19 (11th April 2018) - Lyu, Wei; Alotaibi, Maha; Bell, O. Alexander; Watanabe, Kazuyoshi; Harniman, Robert; Mills, Benjamin M.; Seddon, Annela M.; Rogers, Sarah E.; King, Stephen M.; Yan, Wei; Faul, Charl F. J.
Abstract : An addressable packing parameter approach was developed for reversibly tuning the self-assembly of oligo(aniline)-based supra-amphiphiles. Abstract : We present a newly developed approach to non-covalently address the packing parameter of an electroactive amphiphile. The pH-responsive reversible switching of a tetra(aniline)-based cationic amphiphile, TANI -pentyl trimethylammonium bromide (TANI-PTAB ), between self-assembled vesicles and nanowires by acid/base chemistry in aqueous solution is used to exemplify this approach. Trifluoroacetic acid (TFA ) was selected as a prototypical acid to form emeraldine salt (ES) state (TANI(TFA)2 -PTAB ) vesicles for this new class of small-molecule supramolecular amphiphiles. UV-vis-NIR spectroscopy, transmission electron microscopy (TEM), tapping-mode atomic force microscopy (AFM), and fluorescence spectroscopy were used to investigate the reversible structural transformation from vesicles to nanowires. We show that utilising different protonic acid-dopants forTANI-PTAB can regulate the packing parameter, and thus the final self-assembled structures, in a predictable fashion. We envisage potential application of this concept as smart and switchable delivery systems.